Analisis Penyebab Kerusakan Berkas Rekam Medis Terhadap Efisiensi Pelayanan Kesehatan di RSU Rajawali Citra Bantul Daerah Istimewa Yogyakarta - Muhammad Alif; Eka Yulianta (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
A medical record file is a document that contains information about the patient's identity, health history, examination results, and medical actions that have been taken. This file has an important role in the health service process, both for patients, hospitals, and health workers. Damage to medical record files can cause various kinds of problems that have a negative impact on service efficiency such as delays in providing health services at Rajawali Citra Hospital Bantul Special Region of Yogyakarta. This research uses a qualitative approach. The subjects of the study are the head of the medical record installation, the person in charge of filling and coding, and the medical record filling officer The data collection techniques used are interview methods, observation methods, and documentation methods, which will later obtain primary and secondary data to be analyzed together to draw conclusions. Based on the results of the research that the author has conducted, it can be concluded that the analysis of the causes of medical damage at Citra Bantul Hospital DIY still finds damaged medical record files. The damage to medical record files that I often encounter is medical record files that are torn on the cover and medical record files that are dirty due to dust. So that it has an impact on the effectiveness of health services.